THE INFLUENCE OF LEARNING METHODS AND LEARNING INTEREST ON IPS LEARNING OUTCOMES CLASS VI STUDENTS OF STATE ELEMENTARY SCHOOL 053993 LUBUK KERTANG - Siti Salamah Tanjung; Rahmad Husein; Suratinah Suratinah (Sensei International Journal of Education and Linguistic, 2022)
This study aims to: (1) analyze the differences in students' social studies learning outcomes taught using the PAIKEM method compared to the Picture and Picture method; (2) Analyzing the differences in social studies learning outcomes of students who have high interest in learning compared to students who have low interest in learning; (3) Knowing the interaction between learning methods and students' interest in learning in influencing students' social studies learning outcomes. The sample in this study were 40 students of the State Elementary School Class 053993 Lubuk Kertang in the 2017/2018 academic year. Collecting data in this study through a questionnaire of interest in learning and social studies learning outcomes test. Hypothesis testing is done by using the Two Way Anova test. The results showed that: (1) Social studies learning outcomes of students taught by the PAIKEM method were higher than those of the Picture and Picture method (Fcount = 15,681 and sig. 0.000 > 0.05); (2) Social studies learning outcomes of students who have high interest in learning are higher than students who have low interest in learning (Fcount = 4.395 and sig. 0.043 > 0.05); and (3) There is an interaction between learning methods and interest in learning in influencing students' social studies learning outcomes (Fcount = 7.696 and sig. 0.009 > 0.05).